Generation of stem cell-derived β-cells from patients with type 1 diabetes - Jeffrey R. Millman (Nature Portfolio, 2016)
Pancreatic β cells can be generated from pluripotent stem cells. Here, the authors show that human induced pluripotent stem cells from patients with type 1 diabetes can be differentiated into β-like cells that have no detectable differences compared with cells from non-diabetic individuals.